2021
DOI: 10.3389/fpsyg.2021.632996
|View full text |Cite
|
Sign up to set email alerts
|

Heart and Head: Profiles and Predictors of Self-Assessed Cognitive and Affective Empathy in a Sample of Medical and Health Professional Students

Abstract: For medical and health professions, students learning to respond to others' distress with well-regulated empathy is an important developmental skill linked to positive health outcomes and professionalism. Our study aimed to investigate the sociodemographic, psychological, and psychosocial differences between medical (MS) and health professional (HPS) students and their empathic abilities, since both populations share common stressors, namely, dealing with suffering people. Additionally, we were interested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
0
10
0
1
Order By: Relevance
“…Many Authors showed among medical students an increased risk of depression compared to their peers currently enrolled in non-medical university courses [ 47 , 48 ]. Italian surveys have found that medical students highlighted issues associated with anxiety and depression, emotional distress [ 49 , 50 ], low perceived quality of life [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many Authors showed among medical students an increased risk of depression compared to their peers currently enrolled in non-medical university courses [ 47 , 48 ]. Italian surveys have found that medical students highlighted issues associated with anxiety and depression, emotional distress [ 49 , 50 ], low perceived quality of life [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological impacts of COVID have been felt across the globe; in Italy, university students’ anxiety and depression increased with progression of days in lockdown ( Giusti et al, 2020 ) and in a Spanish population nearly 48% of adults experienced PTSD in response to COVID-19 confinement (Odriozola-Gonzalez et al, 2020). The changes experienced due to COVID-19 may impact future outcomes for medical students; one study found that previous psychological problems and loneliness can cause decreases in empathy, a crucial component of good clinical care ( Giusti et al, 2021a ), while another found that more than 55% of students had significant impairments in concentration and learning abilities due to distance learning ( Giusti et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Such isolation from the restriction, has been shown to affect academic performance in university students, along with negative exacerbation of their mental health symptoms . Many aspects that play a role in the quality of life for students have been impacted by the pandemic and these have been shown to influence the mental health of university students and medical students as well (Giusti et al, 2020;Carletto et al, 2022). In particular, medical students face a higher level of demand and stress than most at baseline, as medical education is considered to be among the most academically challenging and emotionally demanding of higher education programs (Rotenstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%